Fermented Camel Milk (Chal): Chemical, Microbial and Functional Properties - Maryam Salami; Maryam Tamaskani Zahedi; Maryam Moslehishad (Islamic Azad University, 2016)
The aim of this study was to determine physicochemical, microbial properties and antioxidant activity of fermented camel milk (Chal) and introduce it as a functional food. The protein content of the samples was determined using Kjeldahl method and total dry matter using oven drying method. The amount of fat content with Gerber method and pH was measured using a pH meter. Antioxidant activity was also determined using 2,2'-azino-bis-(3-ethylbensothiazoline-6- sulfonic acid) (ABTS) method. The mineral analysis was performed with atomic absorption spectroscopy and microbial count by pour plate method. Results revealed that fat, protein content and total solid determined 5.82±0.27%, 3.07±0.073%, and 12.24±0.16%, respectively. Acidity and pH determined 80±7 °D and 4.52±0.10, respectively. When a food has calcium by itself, this calcium is bonded with the protein of food, this calcium is more effective in our body than the calcium we add to food and they have not bonded any proteins. Adequate calcium consumption may support to decrease the risk of osteoporosis in life. Calcium ranged 103.29±3.87% and phosphorus 10.25±0.1% for Chal samples, respectively. The total counts were equal 6.54±0.19 log CFUmL -1; Coliform count was determined in the ranges of 2.34±0.23 logCFUmL -1 for Chal samples. The results showed that Chal was rich in antioxidant. The antioxidant inhibitory activity of Chal was obtained 45.38%. Diets rich in antioxidants, can inhibit LDL oxidation, influence the activities of immune-competent cells and inhibit the formation of cell-to-cell adhesion factors. Therefore, Chal is introduced as a traditional functional food.